Linking the Declarations of Helsinki and of Taipei: Critical Challenges of Future-Oriented Research Ethics - Kurihara, Chieko; Baroutsou, Varvara; Becker, Sander; Brun, Johan; Franke-Bray, Brigitte; Carlesi, Roberto; Chan, Anthony; Collia, Luis Francisco; Kleist, Peter; Laranjeira, Luís Filipe; Matsuyama, Kotone; Naseem, Shehla; et al. (Frontiers in Pharmacology, 2020)
Expansion of data-driven research in the 21st century has posed challenges in the evolution of the international agreed framework of research ethics. The World Medical Association (WMA)’s Declaration of Helsinki (DoH) has provided ethical principles for medical research involving humans since 1964, with the last update in 2013. To complement the DoH, WMA issued the Declaration of Taipei (DoT) in 2016 to provide additional principles for health databases and biobanks. However, the ethical principles for secondary use of data or material obtained in research remain unclear. With such a perspective, the Working Group on Ethics (WGE) of the International Federation of Associations of Pharmaceutical Physicians and Pharmaceutical Medicine (IFAPP) suggests a closer scientific linkage between DoH and DoT focusing specifically on areas that will facilitate data-driven research, and to further strengthen the protection of research participants.